A 500 year atmospheric dust deposition retrieved from a Mt. Geladaindong ice core in the central Tibetan Plateau - Zhang, Yulan; Kang, Shichang; Zhang, Qianggong; Grigholm, Bjorn; Kaspari, Susan; You, Qinglong; Qin, Dahe; Mayewski, Paul A.; Cong, Zhiyuan; Huang, Jie; Sillanpää, Mika; Chen, Feng (Atmospheric Research, 2015)
A 147-m ice core was retrieved from Guoqu Glacier (33.58°N, 91.18°E, 5750 m a.s.l.) during the Sino–US cooperation expedition on Mt. Geladaindong in the central Tibetan Plateau (TP). In this study, we investigated the high-resolution of atmospheric dust records by using the insoluble particles and crustal ions (Ca2 + and Mg2 +) from the upper 109.93 m segments, covering the period of 1477 to 1982 AD. There existed positive correlations among the ice core dust records themselves and with the dust days from the nearby meteorological stations during the recent decades, indicating that the insoluble particles and crustal ions in the ice core can be used to reconstruct the past atmospheric dust variability. During the past 500 years, the insoluble particles and crustal ions showed high concentrations in the 18th to 19th centuries and low concentrations in the 20th century, corresponding to low and high precipitation in the potential dust source regions. The ice core dust records were positively correlated with the zonal wind and the winter North Atlantic Oscillation (NAO) index, suggesting that NAO may be teleconnected to dust entrainment over the inland TP. This long-term ice core provided an approach to understand the atmospheric dust variability in the central TP during the last 500 years.